Electronic submission in construction: Government approval practice and potential issues in Malaysia - Nurillya, Zahimi; Farouk, A M; Saffuan, Wan Ahmad; Rahimi, A. Rahman (Penerbit UMP, 2024)
Post-COVID-19 has strongly impacted the construction industry worldwide; many parties took alternatives to facilitate the relatively overdue work arrangements. The Malaysian construction industry has been directly affected and has had to increase the adoption of One-Stop Centre (OSC) electronic submissions. According to the Malaysian online system submission policies, it is necessary to obtain construction approval from the OSC through the implementation by town councils. Not understanding the process and documents involved in this procedure might result in ineffective submissions. Hence, the study objectives are to identify: 1) The current submission process and documents for construction approval to town councils, and 2) Issues related to the e-submission process. Semi-structured interviews were conducted with individuals from twenty town (20) city councils in Malaysia to achieve those objectives. The results indicate that the general process includes submitting the required documents through the OSC, validation of submittals, and meeting approvals. The required documents include planning permissions, drawings, engineering plans, environmental management plans, landowner documents, and approvals by other government agencies. Finally, the issues with the e-submission include technical problems and the lack of experience of all involved stakeholders. These findings can be used by policymakers to improve the submission system and industry practitioners in acquiring construction approvals.